Justicia y estrategia: teoría y práctica de las leyes de la guerra en un contexto fronterizo - Fernando Chavarría Múgica (Mélanges de la Casa de Velázquez)
The state of intermittent war between the Spanish and French monarchies during the 16th century closely affected the Pyrenean and Cantabrian border regions. The active participation of the Navarrese and Guipuzcoan communities in the various razzias against the coastal town of St. Jean-de-Luz, particularly that of 1558, was actually driven by private interests despite taking place against a background of generalised conflict between the two crowns. On the one hand, the local powers sought to turn the armed intervention of the monarch to their own advantage; but on the other hand they would have to continue sharing common ground with their neighbours on the other side once the army was demobilised. In accommodating cross-border war between communities with frontier war between monarchies, it was especially important to observe the laws of war (ius in bello), which imposed certain limitations on the conduct of warlike episodes of this kind.